2017
DOI: 10.4038/slja.v25i2.8241
|View full text |Cite
|
Sign up to set email alerts
|

Sedation practices in intensive care units at National Hospital of Sri Lanka

Abstract: There is a marked variation in the use of sedation practices in ICUs worldwide. There is no data on sedation practices in Sri Lankan ICUs. This study was conducted to evaluate sedation practices in intensive care units at National Hospital of Sri Lanka (NHSL) with special emphasis on the use of sedation guidelines, scoring systems, practice of sedation interval and the choice of pharmacological agents. A tick-box questionnaire was used to obtain data from the medical officers in-charge of seven intensive care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Thirteen studies highlighted variations in many aspects of sedation management. Studies are comprised of one qualitative study from Denmark ( Egerod, 2009 ) and 12 quantitative studies: three from the USA ( Gill et al., 2012 ; Guttormson et al., 2010 ; Tanios et al., 2009 ), two from Norway ( Randen and Bjørk, 2010 ; Woien et al., 2012 ), two from UK ( Freilich and Shaw, 2014 ; Yassin et al., 2015 ) and one each from Belgium ( Borkowska et al., 2018 ), France ( The SRLF Trial, 2013 ), Poland ( Kotfis et al., 2017 ), Brazil ( Salluh et al., 2009 ), and Sri Lanka ( Priyankara et al., 2017 ). Within this theme, there are four subthemes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies highlighted variations in many aspects of sedation management. Studies are comprised of one qualitative study from Denmark ( Egerod, 2009 ) and 12 quantitative studies: three from the USA ( Gill et al., 2012 ; Guttormson et al., 2010 ; Tanios et al., 2009 ), two from Norway ( Randen and Bjørk, 2010 ; Woien et al., 2012 ), two from UK ( Freilich and Shaw, 2014 ; Yassin et al., 2015 ) and one each from Belgium ( Borkowska et al., 2018 ), France ( The SRLF Trial, 2013 ), Poland ( Kotfis et al., 2017 ), Brazil ( Salluh et al., 2009 ), and Sri Lanka ( Priyankara et al., 2017 ). Within this theme, there are four subthemes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a study from the USA, which asked the clinical pharmacist to respond on behalf of the ICU, found that the majority (93%) had a sedation assessment tool in use ( Gill et al., 2012 ). Additional studies from Belgium, the USA, and Norway, found that more than 50% of ICU health care staff reported the use or availability of a sedation tool, and similarly, in the UK, Sri Lanka and France, over 50% of ICUs reported its use ( Borkowska et al., 2018 ; Guttormson et al., 2010 ; Randen and Bjørk, 2010 ; Woien et al., 2012 ; Priyankara et al., 2017 ; The SRLF Trial, 2013 ; Yassin et al., 2015 ). Frequently mentioned sedation tools were the 'Richmond Agitation Sedation Scale', the 'Motor Activity Assessment Score' and several versions of the 'Ramsay Scale'.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations